Fatores críticos de sucesso na gestão da EAD nas instituições privadas de ensino superior: um estudo sob a visão dos professores tutores e coordenadores - Alves, Paulo Roberto Feitosa (2018)
The main objective of this work is to identify the Critical Success Factors (FCS) through the view of tutors and coordinators of the EaD courses in the management of Private Higher Education Institutions, in order to reflect on the factors that influence the success of the business. He also sought through the academic research to propose to improve the development of the work in the area of EaD. The growth in the offerings of the EaD courses has stimulated competition, so we should not only think about educating the students, but also about good business management, so it is up to these institutions to be aware of the constant changes that occur in the market. The present dissertation research sought to answer the following question: "What are the critical success factors in the management of EaD in Private Institutions of Higher Education under the vision of tutors and coordinators?" And to seek answers to this question, the The dissertation methodologically opted for the quantitative approach, using as a subject of research the teachers and coordinators of two private higher education institutions located in the State of Rio de Janeiro, in the sense of identifying the FSC in the management of the ED under their eyes and experiences in the teaching-learning process and management. The relevance of this dissertation is to outline the main FSC in the management of EaD, not so that it is a business standard, but rather a guide for the other institutions to be acting in the EaD business.